Bismuth vanadate photoanode synthesized by electron-beam evaporation of a single precursor source for enhanced solar water-splitting - Hwang, Sung Won; Seo, Dong Hyun; Kim, Jin Un; Lee, Dong Kyu; Choi, Kyoung Soon; Jeon, Cheolho; Yu, Hak Ki; Cho, In Sun (Applied Surface Science, 2020)
Bismuth vanadate (BiVO4, BVO) is a promising photoanode material for photoelectrochemical water-splitting, and it is mostly prepared using a sol-gel spin-coating method. BVO often exhibits poor PEC performance without modifications such as doping, co-catalyst deposition, and heterojunction formation. Herein, we report an alternative method to deposit a phase-pure BVO film using the electron-beam evaporation (EB) method. Specifically, electron-beam irradiation on the BVO source generates BVO precursor vapors, depositing an amorphous BVO film. The substrate temperature and emission current (of the electron-beam) were varied to control the phase-purity and grain size of the BVO film. The surface chemical state, optical, and electrochemical properties of the BVO films were characterized using X-ray photoelectron spectroscopy, ultraviolet–visible (UV–Vis) spectroscopy, and electrochemical impedance spectroscopy measurements, respectively. Interestingly, we found that BVO prepared under optimal condition has large grains (~400 nm in lateral size) and oxygen vacancies, thus exhibiting enhanced PEC performance. The photocurrent density of ~1.0 mA/cm2 at 1.23 V versus a reversible hydrogen electrode was obtained, which is 50% higher than the sol-gel derived BVO. The photocurrent density increased further to 2.4 mA/cm2 via CoOx co-catalyst deposition. More importantly, the photocurrent stability of EB-BVO was much higher than the sol-gel BVO.
Keywords: Electrochemical impedance spectroscopy measurements; Electron beam evaporation; Electron beam irradiation; Photoelectrochemical water splitting; Reversible hydrogen electrodes; Sol-gel spin coating method; Solar water splitting; Surface chemical state; Bi-rich surface; BiVO4; E-beam evaporation; Large grains; Oxygen vacancy; Photoelectrochemical water-splitting